A secure and computationally efficient authentication and key agreement scheme for Internet of Vehicles. (October 2021) - Xu, Zisang; Li, Xiong; Xu, Jianbo; Liang, Wei; Choo, Kim-Kwang Raymond
Abstract: In the Internet of Vehicles (IoV), the communication between vehicles and RoadSide Units (RSUs) usually through wireless channels. Therefore, the IoV requires a reliable and secure authentication and key agreement scheme to ensure that the exchanged data in the channel cannot be forged or modified by the adversary. In most existing authentication schemes, the vehicle can only authenticate with a Trusted Authority (TA), which results in the authentication efficiency of these centralized authentication schemes are easily affected by the TA's computational and communication bottlenecks as the increase of traffic density. Therefore, this paper proposes a secure and computationally efficient authentication and key agreement scheme for the IoV, where the RSU can authenticate with the vehicle. Under the analysis of the Real-Or-Random model and the simulation tool ProVerif, the proposed scheme is proved to be secure. Compared with existing schemes, the proposed scheme improves the authentication efficiency and reduces energy consumption.